Creativity, Wellbeing and Mental Health Practice - Gillam, Tony (Palgrave Studies in Creativity and Culture, 2018)
This book argues that some aspects of mental health practice have become mechanical, joyless and uninspiring, leading to a loss of creativity and wellbeing. A high level of wellbeing is essential to mental health and contemporary mental health care - and creativity is at the heart of this. A greater awareness of everyday creativity, the arts and creative approaches to mental health practice, learning and leadership can help us reinvent and reinvigorate mental health care. This, combined with a clearer understanding of the complex concept of wellbeing, can enable practitioners to adopt fresh perspectives and roles that can enrich their work. Creativity and wellbeing are fundamental to reducing occupational stress and promoting professional satisfaction. Introducing a new model of creative mental health care combined with recommendations for wellbeing, Creativity, Wellbeing and Mental Health Practice is a practical, evidence-based book for students, practitioners and researchers in mental health nursing and related disciplines.